(untitled) (Research, Society and Development, 2022)
Polycystic ovary syndrome (PCOS) is one of the most common clinical conditions among endocrine disorders that affect women of reproductive age, accounting for about 80% of cases of anovulatory infertility. Objective to carry out a literature review on the use of metformin in the treatment of women with PCOS, making an analogy in the use of metformin, clomiphene citrate and letrozole. Methodology: The study is an integrated review of the literature as a reference for articles from the years 2013 to 2020 carried out in the databases: Medline, Lilacs, Scielo. Identified on 80 articles, used from 20 in the elaboration of the work. Results: Metformin was shown to be effective as a combination therapy with letrozole in the treatment of PCOS, but there was no consensus on its use as monotherapy.